Improving Elderly Knowledge on Hypertension through Health Education in Parakan Village, Garut - Sadino, Asman; Lubis, Novriyanti; Suryana, Shendi; Prasetiawati, Riska; Hermawan, Belya Anindia; Cahyati, Effan; Apriani, Riza; Karina, Karina; Rena, Rena (Fakultas Kewirausahaan Universitas Garut, 2025)
Hypertension is a non-communicable disease often referred to as a